PENERAPAN MODEL SIMAS ERIC UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI PEMANASAN GLOBAL DI KELAS XI MAN 1 PEKANBARU - Herlina, Misba; Azhar, Azhar; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine the increase in student learning motivation by applying Simas Eric model. This research was conducted at MAN 1 Pekanbaru. This research is a quasi experimental research with nonequivalent control group design research. Population of this research is student of class XI MIA MAN 1 Pekanbaru. The samples were taken from two classes of population based on the homogeneity test and randomly assigned to obtain the experimental class and control class. Data collection was done by giving questionnaires to students before and after learning with the application of Simas Eric on the experimental class and conventional learning in the control class. Descriptive and inferential analysis were used to analyze the data.The result of this research showed n-gain of student's average learning motivation with application of Simas Eric is 0,52 model and n-gain of student's average learning motivation with conventional learning is 0,27 mean that there is an improvement. Based on inferential analysis through independent sample t test sig value was obtained (2-tailed) = 0.00 <0.05 which means there is a significant difference. Thus it can be concluded that the application of Simas Eric model can improve students' learning motivation on global warming material in XI class MAN 1 Pekanbaru.Keywords : simas eric method, learning motivation, global warming material